THE ROLE AND STRUCTURE OF IF CONDITIONALS IN ENGLISH GRAMMAR - Maksimova Zeboxon Nomon qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article provides an  analysis of "if conditionals" in English grammar. Conditional sentences are essential for expressing logical relationships between actions or events. This article provides, types, and usage in academic and general English, providing some examples and discuss the grammatical rules behind every conditional form. A main focus is placed on the vitality of conditionals in fluency and accuracy linguistic.